Hashtag #dragqueenUSA: The Transforming Meaning of Beauty - Nursy, Deici Angelia (Jurnal Bahasa, Sastra, dan Studi Amerika, 2000)
This research aims at understanding how #dragqueeUSA challenge the concept of beauty and examining how #dragqueenUSA offer the plurality of beauty. This research Focuses on the 15 self-images posted in the hashtag takes into account the theory of myth of beauty and performativity act. The examination looks at the flexibility of beauty, the importance of makeup changes, and the relationship between the body and creativity. As a result, the Instagram hashtag #dragqueenUSA presents a fresh interpretation of beauty that eventually gives rise to posthumanism. Thus, the definition of beauty has expanded to include attributes other than just feminine beauty.